Language switching is modulated by emotion priming: evidence from behavioral and event-related potentials study - Wang, Yun; Liu, Xinfang; Liu, Dianzhi; Zhu, Chuanlin (Frontiers in Psychology, 2024)
Introduction Bilinguals often switch between different languages to effectively communicate their ideas. The variation in the increase in reaction times and error rates is termed as the language switch cost. Generally, bilingual language-switching costs demonstrate asymmetry, with a greater cost associated with transitioning from the weaker L2 to the dominant L1 than in the reverse scenario. Recent studies have demonstrated that language switching can be modulated under certain conditions. However, the effect of emotion on language-switching performance is unclear. Therefore, this study aimed to investigate the impact of emotions on bilingual language switching and how this impact manifests across different time windows. Methods This study explored the influence of emotion on language switching between Chinese (L1) and English (L2) using a dual task involving emotion priming and word-picture matching, with concurrent measurement of event-related potentials. Results The behavioral results indicated that a happy mood improved the accuracy and efficiency of L1 switching, while a fearful mood enhanced the efficiency of L2 switching. Electrophysiological data revealed significant interactions among emotion, language, and task in the P1, N2, and N400 stages. Specifically, a happy mood was associated with an increased P1 amplitude during L1 switching, larger N2 amplitudes during L1 repetition, L1 switching, and L2 repetition, as well as greater N400 amplitudes during L1 repetition, L1 switching, and L2 repetition, along with a larger N600 during L2 repetition. Conversely, a fearful mood exhibited a significantly larger N400 during L2 switching and a larger N600 during L2 switching. Discussion The study findings suggest that positive emotions were beneficial for L1 switching in the early stages of visual attention allocation, conflict processing, and lexical-semantic processing. In contrast, negative emotions exhibited a more significant advantage for L2 switching in lexical-semantic processing and deeper levels of semantic processing. This study provides the first electrophysiological evidence for the impact of emotion priming on language-switching performance.